Pengembangan Program Kreatifitas Pembelajaran Santri di Pondok Pesantren Al Hamziyah Wonorejo Pasuruan - M. Misbahul Munir; Barnoto Barnoto (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
The results of this study concluded that the implementation of the learning process at Pondok Pesantren Al Hamziyah Karangmenggah Wonorejo Pasuruan tends to experience positive development and has obtained good results in efforts to develop students' creativity. The indicators can be seen in: (1) the increasing number of students registering as prospective new students, (2) increasing the passing grade of the lowest test scores received as new students, (3) increasing the average score obtained by class III students, (4) increasing growth and the development of educational facilities, (5) increasing the acquisition of championship achievements in the extracurricular field, (6) increasing the quality of graduates who continue to higher education, although the number received is not comparable to the participants who register. From the perspective of empowerment, the results of this study have implications for the development of the learning process broadly, namely the emergence of shared awareness among education managers and teachers that the learning process is not only to transfer knowledge, but also to develop all the potential of students, including the creative potential of students.